A novel tool path strategy for modelling complicated perpendicular curved movements - Meyghani, B. (Trans Tech Publications Ltd, 2019)
Curved surfaces have been widely used in engineering applications such as friction stir welding (FSW), 5 axis CNC machining, and other processes. Therefore, the development of the finite element modelling of the complicated geometries has created a need to determine efficient tool paths. Previous finite element models modelled the single point movement of the tool. However, in industrial applications such as aerospace, mould and die, etc. the movement of the tool is complex. Proper determination of the tool path can lead to substantial savings of the process time, improvement of the workpiece surface quality and the improvement of the tool life, thereby leading to overall cost reduction and higher productivity. This paper presents a new approach for the determination of efficient tool paths in finite element modelling by using ABAQUSÂ® software. VDISP user defined subroutine is used in order to define the complex curved movement of the tool. The results indicate that the method is appropriate for modelling of the tool path, and the tool always has a perpendicular position to the surface. Therefore, the method can be suitable for increasing the application of the finite element modelling in various industries. Â© 2019 Trans Tech Publications, Switzerland